HUBUNGAN TERPAAN IKLAN TV, TERPAAN PROMOSI PENJUALAN DAN KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE VIVO - Muhammad Kholis Nuha; agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Indonesian smartphone users are growing rapidly, several smartphone brands, such as Samsung, Apple, Huawei, Xiaomi, Oppo, and Vivo, are well known by the Indonesian people. In 2020 Vivo has targeted to be ranked second in smartphone market share ownership. To achieve its sales target, Vivo has spent IDR 824 billion in total for TV advertising spending in the 2020 period. In addition, Vivo also carries out sales promotions which are expected to improve purchasing decisions. However, Vivo smartphone market share data in 2021 did not reach the set target and remained in fourth place. This study aims to determine the relationship between advertising exposure and sales promotion exposure to Vivo Smartphone purchase decisions. The theory used in this research is marketing communication theory. The sample used was 65 respondents with the criteria of Domicile in Semarang, Have been exposed to Vivo advertisements, Active users of Vivo smartphones, and 18-35 years old. The results showed that advertising exposure had a significant positive relationship with purchasing decisions for Vivo Smartphone products and exposure to sales promotions had a significant positive relationship with Vivo Smartphone product purchase decisions.